English football - Buraimo, B.; Simmons, R.; Szymanski, S. (Journal of Sports Economics, 2006)
Financial distress is not an uncommon occurrence in English football. The number of clubs falling into financial difficulties has escalated, yet this coincides with an era when the revenues accrued to English football have reached unprecedented levels. This article examines the finances of the Premier League and the Football League and assesses the sources of financial distress experienced by many clubs. The authors find that as clubs in the lower divisions engage in the seasonal race for promotion to higher divisions where financial rewards are greater, excessive wage expenditure and the collapse of a major broadcaster have combined to threaten the already fragile existence of many clubs. The authors assess some policy proposals designed to deal with the financial precariousness of English football.